The effect of music on parameters of fear, pain and anxiety during dental care: an integrative review - Agliati, Dalila de Borba (2018)
OBJECTIVE: Integrative review on the influence of music on parameters of fear, pain and anxiety during dental care.METHODS: Search for articles on the databases MEDLINE, PubMed, LILACS, Scielo and Google Scholar, using the terms “music”, “dentistry”, “music therapy”, “fear”, “pain”, “anxiety” and “music therapy and dentistry”. Inclusion criteria were: randomized clinical trials with primary data surveys that were related only to dentistry. The exclusion criteria were: any other experimental and observational study design, literature reviews and studies in which it was not possible to identify a relation with the subject.RESULTS: Of the 11 randomized trial studies reviewed, all observed beneficial effects in patients who were listening to music during dental care. Studies have shown a reduction of pain during orthodontic treatment, reduction of postoperative recovery time and reduction of anxiety level in pediatric patients.CONCLUSION: It was possible to observe that the use of music is recommended as an accessory therapy in dental care. Nevertheless, for the professional’s success in the treatment of fear, pain and anxiety, dialogue with the patient is essential, giving simple explanations and demonstrations, thus reducing the anxiety caused by the unknown and, in this way, controlling fear and pain. However, it is necessary to carry out more research in this field, in order to obtain better scientific evidence regarding music therapy applied to dental practice.